Importance of lead aVL in the diagnosis of inferior wall myocardial infarction: A case report - Lai Hong Leong; Yoon Chin Yap; Zhen Zhen Lo (Malaysian Family Physician, 2023)
Ischaemic heart disorders are among the leading causes of mortality worldwide. There has been a growing occurrence of heart disease among young adults. Thus, acute myocardial infarction (MI) should be considered in all patients with central chest pain. Herein, we report the case of a young, fit, active smoker with underlying dyslipidaemia presenting with acute MI, characterised by dynamic changes in lead aVL wherein T wave flattening progressed to inversion, suggestive of early reciprocal changes. Soon after, electrocardiogram (ECG) revealed ST elevation in leads III and aVF, indicative of acute inferior wall MI. Subsequently, coronary angiogram showed right coronary artery occlusion. This case report highlights the importance of serial ECGs in patients who present with chest pain and have a high clinical suspicion for acute MI with normal or inconclusive ECG findings. Measurement of highly sensitive serum troponin based on a 1- or 3-h protocol is important in diagnosing acute MI but not ST-elevation MI. An early sign of inferior wall MI may be a new T wave inversion in lead aVL.